Extracurricular Management Increasing Understanding of the Holy Scriptures - Jailani Syahputra Siregar; Mukti, Abdul; Amiruddin Siahaan (JTP - Jurnal Teknologi Pendidikan, 2024)
This research aims to determine extracurricular management to increase understanding of the UPTD holy book. South Labuhanbatu Regency State Elementary School. Methodologically, this research is interactive qualitative research with data collection techniques through document study, interviews and observations. The findings of this study reveal that planning carried out by the South Labuhanbatu Regency Education Office through deliberations/meetings. Organizing is done by developing and delegating tasks professionally and proportionally. It is necessary to delegate tasks so that each element can understand the function of the main tasks and functions because they feel that they have been entrusted with the task so that extracurricular management does not become chaotic and everyone works according to the tasks entrusted. The implementation is carried out by the Regional Government, in this case the South Labuhanbatu Regency Education Service, by providing guidance, direction, advice and motivation. In this case, the leadership always provides good guidance to all related elements, provides positive direction, provides constructive advice, and motivates all related elements, especially school principals and teachers, in carrying out their duties to always be kind. Meanwhile, supervision is carried out by the Regional Government, in this case the South Labuhanbatu Regency Education Service, by monitoring, supervising and evaluating the plans that have been implemented. In this case, the leadership always monitors the implementation of deviant plans. Leaders always evaluate things that are considered not on track. Leaders at every level always go directly into the field to see directly the existing objects.